OUTCOME OF RETROGRADE FLEXIBLE INTRAMEDULLARY NAILING IN FEMORAL DIAPPYSEAL FRACTURES OF CHILDREN - Shahab, Aamir; Hussain, Mumtaz; Imran, Muhammad; Shah, Sana Ali (Pakistan Armed Forces Medical Journal, 2020)
Objective: To evaluate the results of flexible intramedullary nailing in terms of postoperative leg length discrepancy and post operative pain during fracture resolution. Study Design: Case series. Place and Duration of Study: Department of Orthopedic Surgery, Jinnah Hospital Lahore, from Jan 2014 to Dec 2014. Methodology: One hundred and twenty patients (95 boys, 25 girls) having close fractures of femur diaphysis, between age of 5 to 9 years old were stabilized with titanium elastic nails system. Flynn et al scoring criteria was used to evaluate the outcome in terms of leg length discrepancy and visual analogue score for postoperative pain. Results: All patients were evaluated at 8 weeks for postoperative leg pain and leg length discrepancy (LLD). Excellent results (LLD <1cm) were found in eighty nine (89) patients (74.2%) and successful results (LLD <2cm) were found in thirty one (31) patients (25.8%). No patient was found to have a leg length discrepancy >2cm. Fifty four (54) patients (45.00%) had no pain using visual analogue scale (VAS score 0), forty three (43) patients (35.83%) had mild pain (VAS score 1-3), sixteen (16) patients (13.33%) had moderate pain (VAS score 4-6) and seven (7) patients (5.83%) had severe pain (VAS score 7-10) as shown in figure. Conclusion: Titanium elastic nailing syatem is a simple, internally placed splint that acts as load sharing device, respects physis, restores alignment and allows early mobilization. It is preferred treatment in age group (5-9 years) and seems advantageous over other surgical methods.